THE GIARDINO DELLE CAMELIE IN THE BOBOLI MONUMENTAL GARDEN: INTEGRATED SURVEY, STRUCTURAL REINFORCEMENT AND RESTORATION PROJECT OF THE ARCHITECTURE, THE DECORATIONS AND THE HYDRAULIC SYSTEM - G. Tucci (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The Boboli Monumental Garden, from the first half of the 17th century, houses “secret” spaces such as the Giardino delle Camelie, a secluded space reserved only for members of the Medici family. The particular configuration, both in plan and height, and the state of conservation of the Garden required a thorough survey with photogrammetric and laser scanner techniques as a preliminary investigation for the restoration and structural reinforcement project. The survey, together with a careful examination of the present conditions, the historical and archival research, the geognostic investigations enabled to investigate the object in its many specificities and to proceed to the following analysis and design. Starting from the 3D model, it has been possible to extract all the 2D views for the rendering of the survey and project drawings and to achieve countless qualitative and quantitative information on the structures, otherwise difficult to deduce, useful both for the project and restoration.